Avian influenza overview February – May 2020 - Adlhoch, Cornelia (EFSA J, 2020)
Between 16 February and 15 May 2020, 290highly pathogenic avian influenza (HPAI) A(H5) virus outbreakswere reported in Europe in poultry (n=287), captive birds (n=2) and wild birds (n=1)in Bulgaria, Czechia,Germany,Hungary andPolandand two low pathogenic avian influenza (LPAI) A(H7N1) virus outbreaks were reported in poultry in Italy. 258 of 287 poultry outbreaks detected in Europe were secondary outbreaks, suggesting that in the large majoryty of cases the spread of the virus was not due to wild birds.Allthe HPAI outbreaks were A(H5N8) apart from three,which were reported as A(H5N2) from Bulgaria. Genetic analysis of the HPAI A(H5N8) viruses isolated from the eastern and central European countries indicates that this is a reassortant between HPAI A(H5N8) viruses from Africa and LPAI viruses from Eurasia. Two distict subtypes were identified in Bulgaria, a novel reassortant A(H5N2) and A(H5N8) that is persisting in the country since 2016. There could be several reasons why only very few HPAI cases were detected in wild birds in this 2019‐2020 epidemic season and a better knowledge of wild bird movements and virus‐host interaction (e.g. susceptibility of the hosts to this virus) could help to understand the reasons for poor detection of HPAI infected wild birds. In comparison with the last reporting period, a decreasing number of HPAI A(H5)‐affected countries and outbreaks were reported from outside Europe. However, there is considerable uncertainty regarding the current epidemiological situation in many countries out of Europe. Four human cases due to A(H9N2) virus infection were reported during the reporting period from China.